Analyzing the women's empowerment and food security nexus in rural areas of Azad Jammu & Kashmir, Pakistan: By giving consideration to sense of land entitlement and infrastructural facilities. (May 2020) - Aziz, Noshaba; Nisar, Qasim Ali; Koondhar, Mansoor Ahmed; Meo, Muhammad Saeed; Rong, Kong
Highlights: The empirical evidence provides understanding of women's empowerment dimensions that stimulate their food security. The dimensions of ICTS, social support, familial empowerment and legal rights provide significant results with women's own food insecurity. The meager infrastructural facilities create less economic opportunities for women which hinder their food security by making them less self-independent. Lack of sense of land entitlement may also substantially limit women's bargaining power and hamper their access to basic rights even food. Abstract: A rich body of literature exists for explaining the role women play in ensuring their household's food security; however, as far as their own food security is concerned, little attention has been given. Therefore, this research collects evidence on the relationship between women's empowerment and their own food security (access) in the rural areas of Azad Jammu & Kashmir (AJK). Data were collected from the households of 600 rural women. The results provide insights that the domains of legal rights, information and communication technologies (ICTs), social support and familial rights, can be a significant pathway for enhancing the food security of women as more bargaining power of women over the utilization of resources could result in a good quality of food choices and more expense on food items due to these rights. Besides, understanding food insecurity also requires considering gender norms as in this study, the infrastructural facilities and sense of land entitlement provide unexpected non-significant results. Though women help in the mounting necessities of their families, they are unable to enhance the food requirements for themselves due to restricted mobility and less economic opportunities. This is mainly due to the poor infrastructure, and more importantly, the lack of access to resources, especially land, because of lack of knowledge and self-confidence. Notably, the fear of conflict and domestic violence may also impede women from fighting for their rights, which results in poor access to food. Hence, by understanding the household makeup from women's perspectives and customs, the findings from this study can help and guide policymakers in developing more appropriate strategies to improve the food security of women.